Colírio Mnemônico: assinaturas visuais e o papel da linguagem publicitária na construção de seus significados - Costa, Alan Faquinetti da (2017)
The present research proposes to investigate the communicative role of institutional visual signatures, their purposes and their signic characteristics. Banco do Brasil, Bradesco and Itaú, three national financial institutions that are among the most remembered brands in Brazil and among the most valuable banks in the world, were chosen as the study object. The questions that direct this research inquire about the purpose of visual signatures, the ways they acquire meanings, and the role of advertising language, especially its audiovisual elements, in the exemplification that seeks to construct such meanings. In order to answer these questions, the corpus consists of television commercials and the visual signatures (graphic symbols and logos) of the chosen banks. One of the hypotheses of this research is that symbols and logos have, primarily, a mnemonic function that can be subdivided into two: the first is to be fixed in the memory of the public; The second, to evoke positive reminiscences and the narratives of the companies that use them as a signature. Another hypothesis is that, although the graphic elements that make up the visual signatures are capable of reaching the first objective (mnemonic fixation), they can not achieve the second (evocation of narratives). The visual signatures need to be linked to the advertising language, which "teaches" the public to read values in these symbols and typographies. The methodology used to analyze the corpus is the extraction and deconstruction of the texts and the indispensable comparison between them and the companies they refer to. The conclusion reached from this research points to the need for the non-functionalisation of visual signatures, but also indicates the impossibility of this happening in the present time, since commercial competition, while guaranteeing the existence of institutional brands, also feeds the imposition of visibility and closes the door for the "entertainment signature". The theoretical reference is made up of: Andrea Semprini and Gilles Lipovetsky, who base the notions of brand and consumption; Michel Foucault and his work on politics; Leo Huberman and his history of man's wealth; Otavio Ianni and Milton Santos, with their theories on globalization; Lucrécia D'Alessio Ferrara, Claudio Ferlauto, Andre Stolarski and Chico Homem de Melo with their thoughts on graphic design, especially in Brazil; Roberto Corrêa, Lourdes Gabrielli and Tânia Hoff and their works on advertising language; And, finally, Fernando Nogueira da Costa, Niall Ferguson and Noble Foster Hoggson with their historical reflections on the banks